Solanaceous Vegetables and Colorectal Cancer Risk: A Hospital-Based Matched Case-Control Study in Northeast China - Liu, Yang; Li, Simin; Jiang, Liqing; Zhang, Yuchong; Li, Zhi; Shi, Jing (Frontiers in Nutrition, 2021)
Abstract Background: Dietary factors are regarded as essential influence of changing colorectal cancer risk. However, there is no clear conclusion of the relationship between solanaceous vegetables and colorectal cancer at present. The study aimed to evaluate the intake of solanaceous vegetables in relation to colorectal cancer risk among Northeast Chinese population. Methods: We carried out a hospital-based case-control study in three hospitals in Northeast China from 2009 to 2011. The study finally included 833 patients with colorectal cancer and 833 controls matched separately according to age, gender, and resident city. We applied a structural questionnaire to collect demographic characteristics and dietary information by face-to-face interview and adopted conditional logistic regression to calculate odds ratios (ORs) and 95% confidence intervals (CIs). Stratified analyses were conducted by sex and subsite. Results: There was no obvious correlation between total intake of solanaceous plants and colorectal cancer risk. The adjusted OR for the highest quartile and the lowest quartile was 1.00(95%CI: 0.68-1.50). Certain types of solanaceous vegetables were negatively associated with the risk of colorectal cancer, including eggplant (OR = 0.42; 95％CI: 0.29-0.62), sweet pepper (OR = 0.48; 95％CI: 0.33-0.70). Potato was found to have positive correlation with colorectal cancer (OR=1.76; 95%CI: 1.26-2.47). In the stratified analyses by gender, total solanaceous vegetables intake was inversely associated with CRC risk only in men. In the stratified analyses of cancer subsite, no significant association between total solanaceous vegetables intake and colorectal risk was found. Conclusion: No findings showed that the intake of total solanaceous vegetables was related to the reduction of colorectal cancer risk. However, specific types of solanaceous vegetables indicated an inverse association with colorectal cancer risk.